Do Announcement of Private Equity Deals Generate Abnormal Returns: Evidence on Indian Capital Market - Shah, Vikalp (2007)
This project examines an increasingly common form of financing used by Public Companies 'Private Equity' generally referred to as "Private Placements". This dissertation is an empirical study of the short run price reactions to the announcement of Private Equity deals. An empirical study is attempted based on the event study methodology to study the short term price reactions considering an event window of 10 days. The data set comprises of 27 companies which issued 'private equity' from July 2006 - June 2007. The report concludes that there are positive abnormal returns associated to a private equity deal which confirms to the other empirical findings in the area of private placements.